The Kinetics of Thrombin Activity in Recalcified Blood Plasma - Grannis, G. F; Kazal, L. A; Tocantins, L. M (Thrombosis and Haemostasis, 1965)
The kinetics of thrombin formation and inactivation in dilute recalcified plasma were investigated by observing the effects of controlled variations of thromboplastic and antithrombic avtivities on the thrombin activity curve. The entire thrombin activity curve, subsequent to the time thrombin is first detected, can be described by the kinetics of consecutive first order reactions. This observation implies that from determination of the thrombin activity curve and antithrombin activity of plasma, the apparent thromboplastic activity and total prothrombin of plasma can be calculated. It is suggested that the determination of the thrombin activity curve and antithrombin activity of plasma under standardized conditions provides a means for making valid comparisons of plasmas in terms of their potentials for fibrillation.